Proyecto de factibilidad para la creación de una tienda online comercializadora de ropa femenina en la ciudad de Yantzaza, provincia de Zamora Chinchipe - Guamán Paqui, Tania Jazmín (2024)
Currently, the fashion industry has experienced a significant change in the way people purchase clothing, especially with the rise of online shopping. To address this new shopping scenario, the need arises to develop a feasibility project for the creation of an online store and marketing company of women's clothing for the city of Yantzaza, province of Zamora Chinchipe. Methodologically, a descriptive-exploratory research design was applied, with a mixed approach and deductive and inductive methods. To obtain information, a survey was applied to 290 inhabitants of the city of Yantzaza and 40 local leaders who reside in the study area. The results obtained from the survey provided valuable and pertinent data for the construction of a feasibility study, which starts from the market study to the economic-financial evaluation, which support the viability of the creation of the online store, since the financial indicators applied showed the profitability that the company will have during its useful life, supporting the decision to undertake this business. In conclusion, this research has highlighted the fundamental relevance of knowing in depth the needs and preferences of customers to succeed in the online fashion market, which enables the creation of effective strategies, allowing a constant focus on personalizing the customer experience, facilitating rapid adaptation to market trends and exploring opportunities to improve online presence. In this way, the company will be well prepared to maintain a competitive advantage and achieve success in the fashion industry in the city of Yantzaza.